The Dynamics of Various Networks in Transnational Entrepreneurship and Study on Negative Factors to Enterprise among Immigrant Indian Entrepreneurs in UK - a Working Paper - Gangadhar, N.; M. Manohar, B. (International Journal of Engineering and Technology, 2018)
Transnational entrepreneurship has attracted a lot of interest from scholars around the world. The purpose of this paper is to investigate the factors that affect the internationalization of emerging transnational entrepreneurs in UK. This paper has considered only the entrepreneurs who are first generation immigration entrepreneurs who maintain business base in their home country and established a trading relation in the host country.Â  The study focuses on the field of transnational entrepreneurship by proposing an exploratory study on Transnational Enterprise by defining the importance or relevance of different kinds of networks and also to explore the possibilities of negative factors such as bad experiences, dissatisfaction or negative perceptions of their host country, to be an inspiration to venture into transnational entrepreneurship.Â